2017
DOI: 10.1113/ep086064
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐sensitive arterial hypertension, haemodynamic changes and brain metabolites in hypertensive ISIAH rats: MRI investigation

Abstract: Edited by: Kate Denton New Findings r What is the central question of this study?Stress-sensitive arterial hypertension is considered to be controlled by changes in central and peripheral sympathetic regulating mechanisms, which eventually result in haemodynamic alterations and blood pressure elevation. Therefore, study of the early stages of development of hypertension is of particular interest, because it helps in understanding the aetiology of the disease. r What is the main finding and its importance?Non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Of note, we showed previously that E 2 prevents the elevation of arterial chemoreflex during exposures to CIH in female rats, such that an effect of PPT on peripheral chemoreceptors might be expected. It is also relevant to mention that high blood pressure can compromise the cerebral microcirculation, increasing arterial walls and reducing arterial lumen, and high blood pressure also alters metabolism in the brain cortex . In hypertensive patients, a reduced cortical thickness has been reported, a clear sign of cortical damage probably linked to reduced blood perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, we showed previously that E 2 prevents the elevation of arterial chemoreflex during exposures to CIH in female rats, such that an effect of PPT on peripheral chemoreceptors might be expected. It is also relevant to mention that high blood pressure can compromise the cerebral microcirculation, increasing arterial walls and reducing arterial lumen, and high blood pressure also alters metabolism in the brain cortex . In hypertensive patients, a reduced cortical thickness has been reported, a clear sign of cortical damage probably linked to reduced blood perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is also relevant to mention that high blood pressure can compromise the cerebral microcirculation, increasing arterial walls and reducing arterial lumen, and high blood pressure also alters metabolism in the brain cortex. 40,41 In hypertensive patients, a reduced cortical thickness has been reported, 40 a clear sign of cortical damage probably linked to reduced blood perfusion. In that regard, because our results indicate that only PPT reduces arterial blood pressure, while both PPT and DPN prevent the mitochondrial dysfunction and metabolic switch in the brain cortex, we are confident that the central effect of CIH and ERs agonists is not the result of the induction of (or protection against) high blood pressure.…”
Section: Ppt But Not Dpn Prevent the Elevation Of Arterial Blood Pmentioning
confidence: 99%
“…Zfp488 290571 −1.26 zinc finger protein 488 *-genes associated with central nervous system diseases (according to the RGD annotation); ISIAH and WAGrat strains used in the study GABA and glutamate, respectively, are two major inhibitory and excitatory neurotransmitters in the adult mammalian brain [31], which have a direct impact on the sympathetic activity regulation [32]. An earlier study of the metabolic profile in the prefrontal cortex and hypothalamus of 3-month-old ISIAH and WAG rats revealed interstrain differences in the ratio of excitatory and inhibitory brain metabolites, including GABA and glutamate [33]. Based on changes in the expression of the genes Gabra6, Gabrd and Grm2, in common with the metabolomic data, we can assume that there may be changes in the brain stem of ISIAH rats associated with the regulation of sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…On a very interesting side note, arterial pressure is inversely related to HRV in rodent homologs of adolescence but not pre‐adolescence (Tanaka et al, 2000). A study in rats with stress‐induced arterial hypertension showed that hypertension was associated with an attenuation of the excitatory and energetic activity in the PFC (Seryapina, Shevelev, Moshkin, Markel, & Akulov, 2017). In these hypertensive rats, an increase in energetic activity and prevalence of excitatory (glutamate and glutamine) over inhibitory neurotransmitters was noticed (gamma‐aminobutyric acid (GABA) and glycine).…”
Section: A Dynamical Model Of Neurovisceral Integrationmentioning
confidence: 99%